Empowering Agriculture ENERGY OPTIONS FOR HORTICULTURE - NA (No Author) (2009)
This guide has been prepared for use by USAID and its partners to assist local horticulture producers in identifying the electrical, mechanical (shaft horsepower), and thermal requirements for various stages of the horticulture process and to assist these producers in selecting suitable efficient technical options to meet those energy needs. Horticulture, the growing of fruits and vegetables for local and more distant markets, involves the following steps: Land preparation Irrigation Planting and cultivation Harvesting Postharvest handling and packing Cooling and cold storage Transport Processing The amount and the type of energy used in each of these stages reflect the type of horticultural product, scale of operations, financial resources of operators, availability of energy sources and resources, and availability of relevant energy technologies.